Hybrid Topological Derivative-Gradient Based Methods for Nondestructive Testing - A. Carpio; M.-L. Rapún (Abstract and Applied Analysis)
This paper is devoted to the reconstruction of objects buried in a medium and their material properties by hybrid topological derivative-gradient based methods. After illustrating the techniques in time-harmonic acoustic problems with different boundary conditions and in electrical impedance tomography problems with continuous Neumann conditions, we extend the hybrid method for a realistic model in tomography where the boundary conditions are given at a discrete set of electrodes.